On symmetry in the formation of stable partnerships - Jens Gudmundsson (Lund University, School of Economics and Management, Department of Economics, 2011)
In this note, we examine the connection between the roommate model and the partnership formation model (Talman and Yang, 2011, Journal of Mathematical Economics 47, 206-212). Upon noting that both occasionally lack equilibria we look at the stable partnerships model, a combination of the former models and interpretable as one with a social planner. We find two sufficient conditions for the existence of stable matchings in the stable partnerships model, where one relates to efficiency, and one (the symmetry condition) to fairness. Finally, we provide examples from the fair sharing literature on dividing common values that satisfy the symmetry condition.
Keywords: C62; D02; D60; 330; One-sided matching; partnership formation; symmetry condition; stability